Mental health of autistic university students with late diagnosis: Impact on student retention (Research, Society and Development, 2024)
The aim of this study was to analyze the mental health of autistic university students, without Intellectual Disability (ID), with late diagnosis and its impact on academic permanence. Seven autistic individuals, enrolled in a public university, five female and two male, participated. Specific assessments and semi-structured interviews were applied at three different times. The thematic analyses were: impact of late diagnosis; experiences of ableism in family, educational and work contexts; gender issues; mental health; social, sensory and adaptation difficulties; rights; belonging to the university environment; and academic performance. A significant difference was identified in the assessments of anxiety and worry, as well as between the first two assessments of depression. It is discussed that the variable of late diagnosis, in people with autism without ID, results in the absence of interventions in childhood and adolescence, which tend to aggravate mental health conditions in adulthood, especially in relation to independent living and social integration.